Iris biometric model for secured network access - Khoury, Franjieh El. (Boca Raton : CRC Press, 2013)
"The rapid evolution of technology in the computer world has made securing access to confidential data a very important issue in terms of research. This technology is likely to evolve in various architectures. Each architecture has its own functionality, its advantages and disadvantages. On the one hand the transition from a centralized to a decentralized system distributed locally or remotely, has facilitated the tasks in various sectors (i.e., educational, social, government, commercial, etc.). On the other hand, the integration of the Internet has encouraged communication at international level, and allowed operations remotely (i.e., e-commerce, e-banking, etc.). Besides the Internet, there is the mobile network that provides advanced services (i.e., multimedia messaging, Internet access, etc.)"--
pt. 1. State of the art -- pt. 2. Critical analysis of methods of iris recognition -- pt. 3. Our proposed model : the iris crypto agent system -- pt. 4. Implementation and simulations.
"An Auerbach book."
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Biometric identification; Iris (Eye); Computer networks -- Security measures; Electronic books